THE DEVELOPMENT OF INTERACTIVE MEDIA BASED ON ARTICULATE STORYLINE ON STRUCTURE AND FUNCTION OF THE FOOD DIGESTIVE SYSTEM IN HUMANS TOPICS FOR JUNIOR HIGH SCHOOL GRADE VIII - Jahrah Jahrah; Yudha Irhasyuarna; Mella Mutika Sari (Indonesian Journal of Science Education and Applied Science, 2023)
This examination creates articulate storyline learning media which plans to make sense of the legitimacy of the media. This study utilizes a kind of innovative work (Research and development) utilizing the ADDIE cici4d model (examination, plan, improvement, execution, and assessment). This examination just arrived at the improvement stage. The information assortment strategy utilizes a media approval sheet with information investigation utilizing a legitimacy test, to be specific Aiken's V. The consequences of this review show that the media articulate storyline with a media legitimacy trial of 0.81, and a material legitimacy cici4d trial of 0.83 is remembered for the models of high legitimacy or exceptionally substantial. In view of the portrayal above, it is reasoned that the understandable storyline media is fitting for use in science learning.